Chip-budding: A rapid and mass propagation technique for acid lime - Gora, Jagan Singh; Kumar, Ramesh; Jat, Akheram; Kumar , Pawan (Indian Horticulture, 2026)
Acid lime is predominantly propagated through seeds, which results in a prolonged juvenile phase and plants often not being true-to-type. To address these challenges, a comparative study on vegetative propagation methods, including cutting, patch-budding, I-budding, chip-budding, softwood grafting, and wedge grafting, was conducted at ICAR-CIAH, Bikaner during 2019–2025. Among these, chip-budding emerged as the most effective method for rapid and large-scale propagation of quality planting material, achieving over 80–90% success under both in-situ and ex-situ conditions. Chip-budded plants exhibited uniform growth, stronger canopy framework, and precocious bearing within two years. This method combines the benefits of grafting and rootstock influence, facilitating conservation of true-to-type germplasm and supporting crop breeding programs. Adoption of chip-budding is expected to enhance acid lime orchard development, increasing productivity, fruit quality, and profitability for growers.